2015
DOI: 10.1016/j.rmed.2014.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term effects of a physical activity counselling programme in COPD: A randomized controlled trial

Abstract: Our PA counselling programme effectively enhances PA level in COPD patients after three months. Sedentary patients at baseline still benefit after 15 months. ClinicalTrials.gov: registration number NCT00614796.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
181
3
11

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(206 citation statements)
references
References 41 publications
6
181
3
11
Order By: Relevance
“…They offered an identical physical activity counselling intervention to three different patient populations. While the intervention was effective as a stand-alone therapy in patients with moderate impairments in functional exercise capacity it was less effective when offered in combination with a rehabilitation programme in more physically limited patients [30]. These latter patients were most likely perceiving more difficulties in engaging in physical activity, which might explain part of the differences in response.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…They offered an identical physical activity counselling intervention to three different patient populations. While the intervention was effective as a stand-alone therapy in patients with moderate impairments in functional exercise capacity it was less effective when offered in combination with a rehabilitation programme in more physically limited patients [30]. These latter patients were most likely perceiving more difficulties in engaging in physical activity, which might explain part of the differences in response.…”
mentioning
confidence: 98%
“…Patients therefore find it difficult to further increase their participation in daily activities at home while participating in the rehabilitation programme. In a subgroup analysis of a randomised controlled trial, ALTENBURG et al [30] also observed that a physical activity counselling intervention offered during a rehabilitation programme resulted in less improvement than counselling offered as a standalone intervention in less impaired patients. Based on these observations future studies should focus on integrating physical activity coaching elements into the final phase of the rehabilitation programme.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To date, three small randomized controlled trials have explored the effect of pedometers as an adjunct to PR (10)(11)(12). The results were conflicting, reflecting intervention heterogeneity and trial methodologies.…”
mentioning
confidence: 99%
“…DE BLOK et al [77] found a 1000-step difference in increasing daily activity by adding a physical activity counselling programme to a 9-week PR programme, in comparison with a control group. More recently, the effects of pedometer-based programmes in patients with COPD have been investigated in more detail and increases in daily physical activity ranging 600-3000 steps have been reported in comparison with control groups [98][99][100][101][102][103]. Two studies reported a pedometer-based intervention, during which patients were coached by telephone [101,102].…”
Section: Modification Of Patient Behaviourmentioning
confidence: 99%